Diverse properties of store-operated TRPC channels activated by protein kinase C in vascular myocytes - Saleh, Sohag N (Blackwell Science Inc, 2008)
In vascular smooth muscle, store-operated channels (SOCs) contribute to many physiological functions including vasoconstriction and cell growth and proliferation. In the present work we compared the properties of SOCs in freshly dispersed myocytes from rabbit coronary and mesenteric arteries and portal vein. Cyclopiazonic acid (CPA)-induced whole-cell SOC currents were sixfold greater at negative membrane potentials and displayed markedly different rectification properties and reversal potentials in coronary compared to mesenteric artery myocytes. Single channel studies showed that endothelin-1, CPA and the cell-permeant Ca(2+) chelator BAPTA-AM activated the same 2.6 pS SOC in coronary artery. In 1.5 mm [Ca(2+)](o) the unitary conductance of SOCs was significantly greater in coronary than in mesenteric artery. Moreover in 0 mm [Ca(2+)](o) the conductance of SOCs in coronary artery was unaltered whereas the conductance of SOCs in mesenteric artery was increased fourfold. In coronary artery SOCs were inhibited by the protein kinase C (PKC) inhibitor chelerythrine and activated by the phorbol ester phorbol 12,13-dibutyrate (PDBu), the diacylglycerol analogue 1-oleoyl-2-acetyl-sn-glycerol (OAG) and a catalytic subunit of PKC. These data infer an important role for PKC in activation of SOCs in coronary artery similar to mesenteric artery and portal vein. Anti-TRPC1 and -TRPC5 antibodies inhibited SOCs in coronary and mesenteric arteries and portal vein but anti-TRPC6 blocked SOCs only in coronary artery and anti-TRPC7 blocked SOCs only in portal vein. Immunoprecipitation showed associations between TRPC1 and TRPC5 in all preparations but between TRPC5 and TRPC6 only in coronary artery and between TRPC5 and TRPC7 only in portal vein. Finally, flufenamic acid increased SOC activity in coronary artery but inhibited SOCs in mesenteric artery and portal vein myocytes. These data provide strong evidence that vascular myocytes express diverse SOC isoforms, which are likely to be composed of different TRPC proteins and have different physiological functions.